Evil Society in Ursula K. Le Guin’s “The One Who Walk Away from Omelas” - Karomatus Khansyah Ameliyana Putri; Shalimar Noor Rania; Sinta Permatasari; Sufi Ikrima Sa’adah (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2020)
This research analyzes the evil society portrayed in Ursula K. Le Guin’s “The Ones Who Walk Away from Omelas.” The analysis focuses on how the citizens of Omelas commit such an inhuman act in the name of the city’s prosperity, thus, comes the term evil society. This research is descriptive and qualitative in nature. The data are taken from the description of the confined child and the people of Omelas. To elaborate on the portrayal of evil society within the story, the researchers employ Staub’s (1999) concept of evil actions. The concept details the definition of evil and its roots. The findings show that the evil society in the short story is identified by the evil acts that the society commits: the child sacrifice, the citizen’s ignorance, and the abiding laws.